(untitled) (Revista cientifica In Vestigium Ire, 2016)
When referring to the relationship between management and the organization we must know that the administration is the only discipline capable of interpreting the object of study which is the organization itself. Understanding this subject has implied the management thinking to focus its attention on key issues that generate different approaches to different moments in the history of organizations, particularly since the rise of modern capitalism. This article presents evidence of the evolution of general management theory, showing how each school of thought on management offers responses to organizational situations, and how the principles of each theory are applied to different historical moments of the organizations, and at the same time adjusting to new emerging management models.